Unexpected Maternal Convulsion: An Idiopathic Case of Posterior Reversible Encephalopathy Syndrome after Delivery - Jila Agah; Reza Jafarzadeh Esfehani (Mashhad University of Medical Sciences, 2016)
Posterior reversible encephalopathy syndrome (PRES) is associated with various clinical manifestations such as headache, blurred vision, confusion and tonic-clonic convulsion. Some of the predisposing factors for PRES include hypertensive encephalopathy, preeclampsia and eclampsia, lupus erythematosus, thrombotic thrombocytopenic purpura and long-term use of immunosuppressive drugs. This condition rarely occurs after normotensive and uneventful pregnancies. Several theories have been proposed on the etiology of PRES. For instance, endothelial injury and brain edema have been reported as possible causes of PRES. Although PRES is a temporary condition, proper and timely management of the disorder in the acute phase is critical for the prevention of permanent neurological complications. During pregnancy, PRES is normally accompanied with hypertension. In this paper, we present a rare case of PRES in a normotensive pregnancy in a 25-year-old parturient woman (Gravida 2, Ab 1). The patient unexpectedly manifested symptoms of tonic-clonic convulsion one hour after an uneventful vaginal delivery, which were successfully managed. According to our observations, PRES has various clinical manifestations with unexpected occurrence in some cases. Therefore, it is recommended that maternity centers be well-equipped with resuscitation tools, emergency drugs and expert staff so as to manage unforeseen PRES efficiently and prevent permanent maternal neurological complications and mortality.